Armored colloidal photonic crystals for solar evaporation. Issue 38 (21st September 2021) - Wang, Jia-Wei; Wu, Xingjiang; Yu, Xiao-Qing; Guo, Min; Zhao, Jin; Zhu, Liangliang; Chen, Su
Abstract : New core–shell P(St-AA)@PPy colloidal nanoparticles are developed by in situ chemically coupling PPy to P(St-AA) via droplet microfluidic technology, which enables the construction of CPC films towards solar evaporation. Abstract : Colloidal photonic crystals (CPCs) with a highly ordered crystal structure have attracted great attention in displays, colorimetric sensors and solar energy utilization fields. However, the easily cracking microstructure, inferior assembly efficiency and low refractive index contrast result in poor structural colors. Herein, we develop core–shell poly(styrene-acrylic)@polypyrrole (P(St-AA)@PPy) colloidal nanoparticles by the in situ chemical coupling reaction via droplet microfluidic technology. By membrane separation-assisted assembly (MSAA) and electrostatic spraying strategies, the P(St-AA)@PPy colloidal nanoparticles are assembled into the CPC film, which presents high assembly efficiency and saturated angle-independent structural colors, due to the light-absorbing PPy shell and hydrogen-bond interaction between nanoparticles. Benefitting from these outstanding performances, the P(St-AA)@PPy film shows excellent photothermal properties, which can realize a solar vaporization rate of 1.5825 kg m −2 h −1, corresponding to a light-to-vapor efficiency of 94.20%, under 1.0 sun solar irradiance conditions. Our findings open a path for the design of functional CPCs and new-generation photothermal applications.